THE IANGKLUNG MEDIA PLATFORM AS AN INNOVATION IN DIGITAL LEARNING - Andita, Ismiati Dwi; Milyartini, Rita (STKIP Citra Bakti, 2026)
As an initial learning medium before using the angklung musical instrument, students can utilize technology to support the introduction to angklung. iAngklung is an application that offers various features to facilitate students’ learning of the angklung instrument. This study discusses the use of the iAngklung platform as a digital learning innovation in Class XI IPA 7 at SMAN 2 Tasikmalaya. The purpose of this research is to evaluate the effectiveness of the platform in improving students’ conceptual understanding, engagement, and learning motivation. The method employed is a mixed-methods approach with a one-group pretest–posttest design. The results show a significant improvement in students’ conceptual understanding, better student engagement, and increased learning motivation after using iAngklung. Qualitative analysis supports these findings, although several technical challenges were identified. Overall, iAngklung has the potential to serve as an effective learning innovation and supports the development of technology-based learning that integrates local cultural heritage with digital technology.